PENGUKURAN TINGKAT KEMATANGAN TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN MATURITY LEVEL DOMAIN PO DAN AI FRAMEWORK COBIT 4.1 (Jurnal Pilar Nusa Mandiri, 2013)
IT Governance is one important aspect of corporate governance or the institution as a whole. Good IT management will ensure efficiency and achieving quality services to the business goals of the company. Implementation of governance must be well planned in order to be implemented in accordance with the conditions and capabilities. COBIT is a standard model of IT governance that was considered widely. It used because had a appropriate compromise in management scope and processing detail than other ones. The research focused on two main domains of COBIT, Planning and Organization (PO) and Acquisition and Implementation (AI). The research methodology carried out by literature study and vision-mission identification PT Pegadaian (Persero). Next, carried out an awareness management identification toward it’s owned IT function assets to support the achievement of vision and mission the company by questionnaire. By both of data it can be established an expected maturity level suitable for PT. Pegadaian (Persero). Then, the research continued by examination of current maturity level under questionnaire and interview toward the respondents related to the IT governance. The results of this study as  expected data and current maturity levels processes of IT analyzed to find an existing gap, and established an important procedure should be done to hold these gaps to PT. Pegadaian (Persero) with reference to the standard COBIT (Control Objectives for Information and Related Technology).